Blastocystosis y otras infecciones intestinales por parásitos eucarióticos en Gallus gallus domesticus en localidades del sur de Chile - Torres, Patricio (2020)
The purpose of this investigation was to determine the presence and prevalence of blastocystosis, a zoonosis caused by Blastocystis sp in free-range hens in homes of different localities in southern Chile, simultaneously verify human infection in at least one locality, and identify other infections by intestinal parasites in birds. Fresh fecal samples from hens and humans were collected and preserved in PAF fixative and processed by the PAFS method combined with a flotation phase with zinc sulfate solution. Blastocystis sp was detected in half of the homes and the average prevalence was 14.2% in the total of localities being greater in the rural area and in the locality of Teupa (p<0.05). The prevalence in humans was higher than in hens in the town of Ñancul (p<0.05), where the parasite was present in both hosts in 4 of 7 households. The prevalence of infection by Entamoeba gallinarum and the presence of Toxocara spp eggs was similar between localities, but the prevalences of Eimeria spp, Capillariidae gen. spp and Heterakis gallinarum / Ascaridia galli showed differences between localities (p<0.05). Only in Valdivia were observed samples with eggs of Trichostrongylidae gen. spp. The presence of blastocystosis in chicken was detected for the first time in Chile, suggesting its potential transmission to humans. The presence of Toxocara spp eggs in bird faeces suggests that they could act as environmental dispersers.